2010
DOI: 10.2460/ajvr.71.5.564
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous humor and plasma concentrations of ciprofloxacin and moxifloxacin following topical ocular administration in ophthalmologically normal horses

Abstract: Moxifloxacin was better able to penetrate healthy equine corneas and reach measurable AH concentrations than was ciprofloxacin, suggesting moxifloxacin might be of greater value in the treatment of deep corneal or intraocular bacterial infections caused by susceptible organisms. Topical administration of moxifloxacin also resulted in detectable plasma concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Os antifúngicos mais empregados são os derivados poliênicos e azólicos, que atingem os componentes da membrana celular fúngica (CLODE et al, 2010), e os análogos de nucleosídeos (MATTHEWS, 2009). Dentre os derivados poliênicos, citam-se à natamicina e a anfotericina B, e dos derivados azólicos, o miconazol (1%), itraconazol (1%) e o voriconazol (1%) (BROOKS & MATTHEWS, 2007;CLODE et al, 2010). Flucitocina é um análogo de nucleosídeo transportado através da parede celular fúngica e seu uso clínico restringe-se ao tratamento de Candida spp.…”
Section: Tratamento Médicounclassified
“…Os antifúngicos mais empregados são os derivados poliênicos e azólicos, que atingem os componentes da membrana celular fúngica (CLODE et al, 2010), e os análogos de nucleosídeos (MATTHEWS, 2009). Dentre os derivados poliênicos, citam-se à natamicina e a anfotericina B, e dos derivados azólicos, o miconazol (1%), itraconazol (1%) e o voriconazol (1%) (BROOKS & MATTHEWS, 2007;CLODE et al, 2010). Flucitocina é um análogo de nucleosídeo transportado através da parede celular fúngica e seu uso clínico restringe-se ao tratamento de Candida spp.…”
Section: Tratamento Médicounclassified
“…However, a study in horses showed significant serum levels of moxifloxacin after topical administration of ophthalmic moxifloxacin, as compared to ophthalmic ciprofloxacin, which resulted in undetectable levels in the serum 8 . Risk factors associated with systemic fluoroquinolone-induced tendon disorders include age > 60 years, history of corticosteroid therapy, renal failure, diabetes mellitus, and a history of musculoskeletal disorders 9 .…”
Section: To the Editormentioning
confidence: 99%